(untitled) (The Peerian Journal, 2024)
This article discusses the goals of teaching English for Special Purposes (ESP) in the context of professional medical communication. The importance of communicative language learning for students of higher medical institutions and other medical personnel is emphasized. The language skills and knowledge for effective communication in the specific professional and academic medical context in which they need to use English are discussed. The author also defines the necessary linguistic and communicative competencies for the medical field. Professional practical learning situations are considered as effective learning strategies for ESP